2006
DOI: 10.1101/gad.380906
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for Xist RNA in the formation of a repressive nuclear compartment into which genes are recruited when silenced

Abstract: During early mammalian female development, one of the two X chromosomes becomes inactivated. Although X-chromosome coating by Xist RNA is essential for the initiation of X inactivation, little is known about how this signal is transformed into transcriptional silencing. Here we show that exclusion of RNA Polymerase II and transcription factors from the Xist RNA-coated X chromosome represents the earliest event following Xist RNA accumulation described so far in differentiating embryonic stem (ES) cells. Parado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
536
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(579 citation statements)
references
References 62 publications
39
536
0
4
Order By: Relevance
“…This mass action requirement for silencing might reflect a high concentration of specific transposable-element-binding proteins similar to CENP-Bs capable of recruiting chromatin modifiers. The formation of Tf bodies could have parallels in mammalian X-chromosome inactivation, in which transposable elements might facilitate the assembly of a silent nuclear compartment [45][46][47] . Recent evidence suggests that whereas RNAi has a prominent role in silencing transposable elements in germ cells in higher eukaryotes 7 , there are probably alternative mechanisms, possibly similar to that of S. pombe CENP-B-based surveillance, for regulating transposable elements in somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…This mass action requirement for silencing might reflect a high concentration of specific transposable-element-binding proteins similar to CENP-Bs capable of recruiting chromatin modifiers. The formation of Tf bodies could have parallels in mammalian X-chromosome inactivation, in which transposable elements might facilitate the assembly of a silent nuclear compartment [45][46][47] . Recent evidence suggests that whereas RNAi has a prominent role in silencing transposable elements in germ cells in higher eukaryotes 7 , there are probably alternative mechanisms, possibly similar to that of S. pombe CENP-B-based surveillance, for regulating transposable elements in somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…A-repeat deficient RNA is also able to recruit macroH2A, SAF-A and Ash2L [45]. Either these proteins interact with regions of Xist RNA other than the A-repeats or their recruitment is secondary to the establishment of a transcriptionally silent domain that occurs using A-repeat deficient transgenes [58]. As discussed earlier, it has been suggested that the silent domain corresponds to common repeat sequences on the X chromosome and it follows that these could also be the site of recruitment of other factors.…”
Section: Discussionmentioning
confidence: 99%
“…DNA-FISH using X-linked sequences showed that while repetitive sequences on the X chromosome are included in the domain of Xist RNA lacking the A-repeat, genic regions are often found outside or at the periphery of the domain [58]. These findings raise the idea that one role of Xist RNA is to create a transcriptionally silent domain that represses repetitive sequences by recruiting PRCs and by excluding rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20110325 RNAPII in a manner independent of A-repeat function, and a second role is to incorporate genic regions on the X chromosome from outside or at the periphery of the Xist RNA domain into the interior in a manner dependent on the A-repeat.…”
Section: Rstbroyalsocietypublishingorg Phil Trans R Soc B 368: 2011mentioning
confidence: 99%
“…A conserved sequence on the 5 0 of Xist, which has been termed repeat A, is required for gene silencing (Wutz et al, 2002). Expression of Xist lacking repeat A does not cause gene repression but results in localization of Xist and recruitment of most chromatin modifications to the Xi (Chaumeil et al, 2006). The repeat A RNA motif is predicted to fold into a stem loop structure, which could function as a binding site for silencing factors (Wutz et al, 2002).…”
Section: Inactivation In Mammalsmentioning
confidence: 99%
“…In mice, Xist RNA forms a domain over the non-genic chromatin of the core of the X chromosome territory (Chaumeil et al, 2006). Also on the human Xi XIST seems to overlap the central region of the chromosome territory, which contains mostly genomic repeats (Clemson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%